Strain engineering of 2D NEMS for resonant sensing - More, Swapnil; Naik, Akshay advised (Bangalore : IISc, 2023)
2D material-based nanoelectromechanical systems have emerged as excellent tools for force measurement with extreme sensitivity levels. Most sensing methods with 2D nanoelectromechanical (2D NEMS) systems utilize frequency tuning of the resonant mode in response to external stimuli. However, the interaction of the harsh external stimulus with the delicate 2D NEMS limited these devices$1 (Butility only in the research labs. We propose a fabrication and packaging method for 2D NEMS devices to extend their application outside the research labs. Under the proposed scheme, the 2D NEMS is coupled to the external stimulus through substrate strain. The substrate acts as a protective barrier between the NEMS and the environment. At the same time, the substrate also influences the strain on the 2D NEMS. The external stimulus changes the strain on the substrate and hence on the 2D NEMS device. The strain change on 2D NEMS changes the frequency of vibration modes. 2D materials such as graphene have a high Young$1 (Bs modulus.s
include bibliographic reference and index
PhD; 2023; Centre for nano science and engineering
Keywords: 2D Materials; nanoelectromechanical systems; graphene